Data on gender representation in food and beverage print advertisements found in corner stores from Guatemala and Peru - Rozas Urrunaga, Lucila Jimena (2021)
Data on gender representation in food and beverage advertisements may allow for a better understanding of how the food industry is targeting different audiences based on gender. Nonetheless, scant research on food and beverage print advertising with a gender approach has been conducted. Therefore, we sought to assess the prevalence of gender focus in print advertisements found inside corner stores in two cities: Guatemala City, Guatemala, and Lima, Peru. Data description: We developed two complementary datasets as part of the study: (1) a dataset of digital photographs of 200 food and beverage print advertisements found in corner stores located near schools (100 ads per country selected according to criteria such as product type, image quality, and uniqueness); (2) a quantitative dataset with data of the content analysis of these photographs. We employed 19 variables to record the general information and gender assessment of the ads. These datasets should allow scholars and public officials to identify gender-specific marketing strategies of the food industry that might impact children’s and adolescents’ nutrition differently.